2008
DOI: 10.1128/jvi.00719-08
|View full text |Cite
|
Sign up to set email alerts
|

Viral Genome Methylation as an Epigenetic Defense against Geminiviruses

Abstract: Geminiviruses encapsidate single-stranded DNA genomes that replicate in plant cell nuclei through doublestranded DNA intermediates that associate with cellular histone proteins to form minichromosomes. Like most plant viruses, geminiviruses are targeted by RNA silencing and encode suppressor proteins such as AL2 and L2 to counter this defense. These related proteins can suppress silencing by multiple mechanisms, one of which involves interacting with and inhibiting adenosine kinase (ADK), a cellular enzyme ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
325
2
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(385 citation statements)
references
References 69 publications
20
325
2
20
Order By: Relevance
“…AGO4 is also involved in plant defense against DNA viruses. In tissues that have recovered from infection, DNA of Beet curly top virus L2 2 mutant is hypermethylated and host recovery requires AGO4 (Raja et al, 2008), suggesting that DNA methylation mediated by AGO4 is a mechanism used by plants to defend against DNA viruses. Rice encodes four AGO4 homologs (AGO4a, AGO4b, AGO15, and AGO16) (Kapoor et al, 2008).…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…AGO4 is also involved in plant defense against DNA viruses. In tissues that have recovered from infection, DNA of Beet curly top virus L2 2 mutant is hypermethylated and host recovery requires AGO4 (Raja et al, 2008), suggesting that DNA methylation mediated by AGO4 is a mechanism used by plants to defend against DNA viruses. Rice encodes four AGO4 homologs (AGO4a, AGO4b, AGO15, and AGO16) (Kapoor et al, 2008).…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…Recent research has indicated that transcriptional gene silencing (TGS) caused by small RNA-guided methylation is also a defense mode against DNA viruses [65]. Tomato yellow leaf curl China virus (TYLCCNV), a member of the geminiviruses, has a satellite RNA called DNA  (betasatellite).…”
Section: Resultsmentioning
confidence: 99%
“…Étant donné qu'AGO2, AGO4 et AGO7 recrutent majoritairement les sARN avec une adénosine en 5'-terminal et AGO5 les sARN commençant par une cytosine, leur association avec le RISC antiviral n'est pas à exclure [24,32,33]. De même, AGO4 et AGO6 étant responsables du silencing transcriptionnel chez Arabidopsis, leur rôle potentiel dans la défense contre les virus à ADN est probable [34,35].…”
Section: Revuesunclassified